Burnout as a Predictor of Quality of Life Among the Federal Road Safety Corps Employees in Benue State Sector Command - Zakariah, Danladi; Akafa, Vika Tensaba; Akafa, Tensaba Andes; Oladele, Gloria Omonefe; Iseko, Kingsley Iyoko; David, Izam Emmanuel; Ujah, Oche Williams (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2024)
This study investigated the relationship between burnout and quality of life among the Federal Road Safety Corps Employees in Benue State Sector Command. The study employed cross sectional and expost facto design where 200 participants consisting of 161 (80.5%) males, 37 (18.5%) females and 2 (1.0%) did not indicate their sex. Their ages ranged from 21-60 years with means age of 35.55 (SD=7.21). Maslach Burnout Inventory (MBI) and quality of Life Scale (WHOQOL) were used for data collection using Multistage, Stratified random and systematic sampling techniques. Statistical analysis involved the use of multiple regressions. Findings indicated that, there was a significant negative relationship between burnout and quality of life among the Federal Road Safety Corps Employees in Benue State Sector Command. The result of the finding reviewed that there was a significant negative relationship between burnout and the overall quality of life among the Federal Road Safety Corps employees in Benue State Command [R=.562, R2=.316, F (3,178)=27.376, p<.001]. This implies that burnout accounted for 31.6% of the total variance observed in quality of life among the Federal Road Safety Corps employees in Benue State Sector Command. The result of the study also showed the individual contributions of the various dimensions of burnout to overall quality of life which indicated that emotional exhaustion made the highest significant negative contribution (β=-.414, t=-5.180, p<.001) followed by depersonalization (β=-.235, t=-3.081, p<.01) while personal accomplishment made no significant contribution to the model (β=.027, t=.355, p>.05) respectively. Based on the findings of this study, it was recommended that conscious efforts should be made to enhance quality of life among the Federal Road Safety Corps Employees through reduction of burnout stress inherent in the work place among the Federal Road Safety Corps Employees in Benue State Sector Command and Nigeria at large.